Molar tooth development in caspase-3 deficient mice - Matalova, Eva; Sharpe, Paul T; Lakhani, Saquib A; Roth, Kevin A; Flavell, Richard A; Setkova, Jana; Misek, Ivan; Tucker, Abigail S (The International journal of developmental biology, 2006)
Tooth morphogenesis is accompanied by apoptotic events which show restricted temporospatial patterns suggesting multiple roles in odontogenesis. Dental apoptosis seems to be caspase dependent and caspase-3 has been shown to be activated during dental apoptosis.Caspase-3 mutant mice on different genetic backgrounds were used to investigate alterations in dental apoptosis and molar tooth morphogenesis. Mouse embryos at E15.5 were analyzed to reveal any changes in enamel knots, which are transient structures eliminated by apoptosis. In caspase-3(-/-) mice on the B57BL/6 background, disorganization of the epithelium was found in the original primary enamel knot area and confirmed by altered expression of Shh. Despite this early defect in molar tooth development, these mutants showed correct formation of secondary enamel knots as indicated by Fgf-4 expression. Analyses of adult molar teeth did not reveal any major alterations in tooth shape, enamel structure or pattern when compared to heterozygote littermates. In caspase-3(-/-) mice on the 129X1/SvJ background, no defects in tooth development were found except the position of the upper molars which developed more posteriorly in the oral cavity. This is likely, however, to be a secondary defect caused by a physical squashing of the face by the malformed brain. The results suggest that although caspase-3 becomes activated and may be essential for dental apoptosis, it does not seem fundamental for formation of normal mineralised molar teeth.
Keywords: hybridizace in situ; Fibroblast Growth Factor 4; Hedgehog Proteins; RNA, Messenger; Caspase 3; Mice, Knockout; fibroblastový růstový faktor 4; kaspasa 3; vývojová regulace genové exprese; Cell Proliferation; Odontogenesis; Molar; Gene Expression Regulation, Developmental; In Situ Hybridization; Tooth Germ; zubní sklovina; myši knockoutované; Caspases; kaspasy; trans-aktivátory; Dental Enamel; zubní zárodek; Animals; moláry; proteiny hedgehog; odontogeneze; zvířata; myši; apoptóza; Trans-Activators; proliferace buněk; Mice; messenger RNA; Apoptosis